2021
DOI: 10.1109/access.2021.3135604
|View full text |Cite
|
Sign up to set email alerts
|

Segment-Based CO₂ Emission Evaluations From Passenger Cars Based on Deep Learning Techniques

Abstract: The overall level of emissions from the Swiss passenger cars is strongly dependent on the fleet composition. Despite technology improvements, the Swiss passenger cars fleet remains emissions intensive. To analyze the root of this problem and evaluate potential solutions, this paper applies deep learning techniques to evaluate the inter-class (namely micro, small, middle, upper middle, large and luxury class) and intra-class (namely sport utility vehicle and non-sport utility vehicle) differences in carbon diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…After the cleaning, the dataset included vehicle production years ranging from 1980 to 2023. However, literature indicates that the evolution of vehicle features over time can substantially hinder classification efforts 5,28,35,36 . Our analysis (see the Discussion section), supports this view, suggesting that a broad temporal range may negatively impact classification accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the cleaning, the dataset included vehicle production years ranging from 1980 to 2023. However, literature indicates that the evolution of vehicle features over time can substantially hinder classification efforts 5,28,35,36 . Our analysis (see the Discussion section), supports this view, suggesting that a broad temporal range may negatively impact classification accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the definition of a passenger car covers a spectrum of vehicle types, sizes, and uses: from small, 2-seat bubble cars to large family vans. The variation of passenger cars' characteristics translates into variability in energy consumption and related Greenhouse Gas (GHG) emissions 5,6 . Consequently, several studies have identified fleet composition as one of the key drivers of the overall emissions and fuel consumption performance of the sector [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the global depletion of fossil resources and, as a result, rising crude oil costs pose a signifcant challenge to the vehicle industry. Electric vehicles (EVs) have already been widely adopted in the automotive industry as the most promising substitutes for decreasing CO 2 emissions and global warming concerns [2]. Te most popular EVs, such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and pure electric vehicles or battery electric vehicles (BEVs), have become popular options due to their ability to address the issues that fossil fuel vehicles pose.…”
Section: Introductionmentioning
confidence: 99%